AAPHD 2002 Special Merit Award for Outstanding Achievement in Community D entis try-Int ernational: Patricia Main, DDS, DDPH, MSc - Robert J. Weyant, DMD, DrPH (Blackwell Synergy, 2002)
This appears to be an award for having fun. All the projects that I worked on with MHD, including the Web site, the list-serv, the Executive Council, and the Residency Director’s Workshops were not only a great learning experience, but also a lot of fun. Thanks for the award; it is greatly appreciated